The school, a key social space for peruvian democratization: A study comparing the traditional educative proposal and an alternative educative proposal (Revista Peruana de Investigación Educativa, 2009)
the investigation focused its efforts in analyzing how is it that school assumes the roles of formation and socialization of democratic individuals, not only with theoretical knowledge, but also as subjects capable of reproducing social discourses and practices of the democratic kind in their everyday life and in their relationship to their peers and their social environment. the school was chosen as the object of study, firstly because it’s the only recognized institution with the goal of forming future generations; and secondly because it presents itself as the first space in which people formally relate to all that is public. the study had a methodology of case study of two distinct educative proposals, one that we denominate “traditional” and another one known as “alternative” to analyze if there were differences in the democratic formation of students. theoretically the research was based on a thinking current 2 , which states that democracy is founded on individuals’ freedom, the formation of a political community and citizen’s formation. Starting on this perspective, three democratic qualities were identified to evaluate the achievements of each school in the process of democratic formation: social commitment, public participation and individual normativity management. the results showed, on one side, the attitude differences in students from both schools in relation the dimensions of the study and on the other hand, presented evidence that the analyzed alternative proposal is facilitating in a greater measure the development of democratic disposition in their students, compare to the other proposal.
Keywords: democracy; Education; Citizenship; Socialization; School